Redox dynamics in the active layer of an Arctic headwater catchment; examining the potential for transfer of dissolved methane from soils to stream water. Issue 11 (5th November 2016) - Street, Lorna E.; Dean, Joshua F.; Billett, Michael F.; Baxter, Robert; Dinsmore, Kerry J.; Lessels, Jason S.; Subke, Jens‐Arne; Tetzlaff, Doerthe; Wookey, Philip A.
Abstract: The linkages between methane production, transport, and release from terrestrial and aquatic systems are not well understood, complicating the task of predicting methane emissions. We present novel data examining the potential for the saturated zone of active layer soils to act as a source of dissolved methane to the aquatic system, via soil water discharge, within a headwater catchment of the continuous permafrost zone in Northern Canada. We monitored redox conditions and soil methane concentrations across a transect of soil profiles from midstream to hillslope and compare temporal patterns in methane concentrations in soils to those in the stream. We show that redox conditions in active layer soils become more negative as the thaw season progresses, providing conditions suitable for net methanogenesis and that redox conditions are sensitive to increased precipitation during a storm event—but only in shallower surface soil layers. While we demonstrate that methane concentrations at depth in the hillslope soils increase over the course of the growing season as reducing conditions develop, we find no evidence that this has an influence on stream water methane concentrations. Sediments directly beneath the stream bed, however, remain strongly reducing at depth throughout the thaw season and contain methane at concentrations 5 orders of magnitude greater than those in hillslope soils. The extent of substreambed methane sources, and the rates of methane transport from these zones, may therefore be important factors determining headwater stream methane concentrations under changing Arctic hydrologic regimes. Key Points: CH4 formed in saturated soils above permafrost can influence surface water CH4 budgets via soil water discharge We show novel data on redox dynamics and CH4 in hillslope permafrost soils and the potential for transport to streams Hillslope soils become anoxic as thaw deepens and CH4 content increases but we find no evidence of a link to stream CH4